2013
DOI: 10.1103/physreva.88.013823
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity of photon propagation in electromagnetically induced transparency in the presence of four-wave mixing

Abstract: We study the effects of four-wave mixing (4WM) in a quantum memory scheme based on electromagnetically induced transparency (EIT). We treat the problem of field propagation on the quantum mechanical level, which allows us to calculate the fidelity of propagation for a quantum light pulse such as a single photon. While 4WM can be beneficial for classical, all-optical information storage, the quantum noise associated with the signal amplification and idler generation is, in general, detrimental for a quantum mem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 23 publications
2
62
0
Order By: Relevance
“…Following the treatment in [24,31] for the double-Λ scheme in the approximation of negligible spin coherence relaxation rate (γ gs = 0, ), the output fields can approximately be expressed for resonant fieldŝ…”
Section: Theorymentioning
confidence: 99%
“…Following the treatment in [24,31] for the double-Λ scheme in the approximation of negligible spin coherence relaxation rate (γ gs = 0, ), the output fields can approximately be expressed for resonant fieldŝ…”
Section: Theorymentioning
confidence: 99%
“…There it was found that while fluorescence noise was negligible for off-resonant storage of short pulses, the thermal noise contributed by four-wave mixing destroyed the anti-bunching characteristic of single photons. Fourwave mixing noise is therefore the key roadblock preventing the implementation of Λ-memories at room temperature [27,28]. Suggested solutions to this problem include partial suppression via polarisation selection rules [29], and engineering a Raman absorption feature in an isotopically mixed vapour [30].…”
Section: Introductionmentioning
confidence: 99%
“…However, large control pulse energies are needed to drive the storage interaction far from resonance, and the control can also drive unwanted four-wave mixing, introducing noise which cannot be filtered out either spectrally or temporally. Four-wave mixing noise has emerged as the last remaining roadblock to the development of efficient Λ-type room-temperature quantum memories [17,[20][21][22][23]. We solve this problem by introducing a new cavity enhanced Raman memory protocol.…”
mentioning
confidence: 99%